The Effect of Financial Literature, Lifestyle and Income of Parents on Student Financial Management Behavior - Mashud Mashud; Mediaty Mediaty; Grace T. Pontoh (AIBPM Publisher, 2021)
This This study aims to examine the effect of financial literacy, lifestyle and parental income on student financial management behavior. This research is quantitative research using an analytical tool, namely the Statistical Product and Service Solution or SPSS software. The population in this study were active students of STMIK AKBA in the information systems study program. The sampling technique used is simple random sampling, which is a random sampling technique without regard to the existing strata in the population. The number of samples in this research is 125 students. Data collection techniques used questionnaires and observations with financial literacy variables (X1), Lifestyle (X2), parents' income (X3) and financial management behavior (Y). The results showed that financial literacy had a positive and significant effect on the financial management behavior of students, while the lifestyle and income of parents had no effect on the financial management behavior of STMIK AKBA students.